Interaction between subjective well-being, Economic activity and education in the EU - Gataūlinas, Artūras; Zabarauskaitė, Rasa (Business: Theory and Practice, 2014)
The article examines the impact of professional wellbeing of EU citizens on their life satisfaction at both micro and macro levels. The following indicators were selected to describe the professional wellbeing: involvment in the official employment, level of education, and job satisfaction. The findings of the article suggest that employed respondents evaluated their subjective wellbeing significantly higher as compared to those not participating in the labour market. Similar findings were drawn when comparing subjective wellbeing of the respondents in relation to their education. Respondents with higher education reported significantly higher statistically proven subjective wellbeing than those with lower education. In the article, the interpretation of the findings is based on the conceptual model of subjective wellbeing of needs as well as on the role of employment and education in satisfaction of physiological and socially acceptable needs of individuals. Work activity is more directly linked with the satisfaction of individual needs than education. However, engagement in work has only an impact on subjective wellbeing if work activity is perceived as job satisfaction. If employment is perceived by individuals as providing greater satisfaction, it tends to make a more positive impact on the subjective wellbeing of individuals compared to activities that are perceived as providing less satisfaction. Subjektyviosios gerovės sąveika su darbine veikla ir išsilavinimu ES šalyse Santrauka Straipsnyje siekiama įvertinti išsilavinimo, darbinės veiklos ir pasitenkinimo darbu poveikį ES šalių gyventojų subjektyviajai gerovei. Profesinei gerovei aprašyti pasirinkti tokie rodikliai, kaip dalyvavimas oficialioje darbinėje veikloje, išsilavinimo lygis ir pasitenkinimas darbu. Analizės metu nustatyta, kad darbinėje veikloje dalyvaujantys respondentai statistiškai reikšmingai palankiau vertina savo subjektyviąją gerovę nei darbinėje veikloje nedalyvaujantys respondentai. Taip pat ir respondentai, turintys aukštesnį išsilavinimą, statistiškai reikšmingai palankiau įvertino savo subjektyviąją gerovę nei turintys žemesnį išsilavinimą respondentai. Tokios tendencijos aiškinamos tuo, kad darbinė veikla suteikia individui geresnių galimybių tenkinti fiziologinius ir socialiai priimtinus poreikius, o aukštesnis išsilavinimas sudaro geresnių galimybių pasirinkti darbinę veiklą. Taip pat straipsnyje nustatytas stiprus koreliacinis ryšys tarp subjektyviosios gerovės ir pasitenkinimo darbu makrolygmeniu. Tai reiškia, kad šalyse, kuriose vidutinis pasitenkinimas darbu yra aukštesnis, vidutinė subjektyvioji gerovė taip pat turi tendenciją būti aukštesnė. Reikšminiai žodžiai: subjektyvi gerovė, pasitenkinimas darbu, išsilavinimas, profesinė gerovė.